In Vitro Effect of Hydroalcoholic Extract of Aloe Vera and 0.2% Chlorhexidine Mouthwash on Streptococcus Sanguinis, Streptococcus Salivarius and Streptococcus Mutans - Shakerian, Mohadese; Yaghoti, Mohamad Mehdi; Doostaki, Soheila (Journal of Dental School, 2019)
Objectives This study aimed to assess the antimicrobial effects of aloe vera hydroalcoholic extract and 0.2% chlorhexidine (CHX) mouthwash on Streptococcus sanguinis (S. sanguinis), Streptococcus salivarius (S. salivarius) and Streptococcus mutans (S. mutans) in vitro. Methods Four concentrations (25%, 50%, 75% and 100%) of hydroalcoholic extract of aloe vera were prepared. S. sanguinis, S. salivarius and S. mutans were cultured on tryptic soy agar, and a single colony was removed from each microorganism and the opacity of pure microbial suspension was set at 0.5 McFarland standard concentration. Brain heart infusion broth culture medium, different concentrations of aloe vera extract, 0.2% CHX mouthwash, negative (distilled water) and positive (penicillin) controls and 0.5 McFarland bacterial suspension were added to the tubes and incubated at 37°C for 5, 10, and 15 minutes. Then, the samples were cultured on tryptic soy agar and incubated at 37°C for 48 hours. Number of colony forming units (CFUs) in the groups was compared with two-way repeated measures ANOVA. For paired comparisons, Tukey's multiple comparisons test was used (P˂0.05). Results The results showed significant effect of hydroalcoholic extract of aloe vera (25, 50, 75, and 100%) on the tested microorganisms but the mean CFUs following the use of 0.2% CHX was significantly less than that after using different concentrations aloe vera extract (P<0.001). Regardless of the type of the material, the number of CFUs decreased with increased exposure time. Conclusion Aloe vera can be used alone or with CHX mouthwash to eliminate cariogenic bacteria.